Opioid-induced constipation: advances and clinical guidance. (March 2016) - Nelson, Alfred D.; Camilleri, Michael
Currently opioids are the most frequently used medications for chronic noncancer pain. Opioid-induced constipation is the most common adverse effect associated with prolonged use of opioids, having a major impact on quality of life. There is an increasing need to treat opioid-induced constipation. With the recent approval of medications for the treatment of opioid-induced constipation, there are several therapeutic approaches. This review addresses the clinical presentation and diagnosis of opioid-induced constipation, barriers to its diagnosis, effects of opioids in the gastrointestinal tract, differential tolerance to opiates in different gastrointestinal organs, medications approved and in development for the treatment of opioid-induced constipation, and a proposed clinical management algorithm for treating opioid-induced constipation in patients with noncancer pain.